Short-Term Equity Trading Practices of Institutional Investors: Evidence from Property-Casualty Insurers in the United States - Jin Park; Tim Query (Economic Review: Journal of Economics and Business, 2013)
In addition to premiums, investment income is one of the two main sources of capital for property-casualty (P/C) insurance companies. This study investigates short-term equity trading behavior of P/C insurers in the United States in 2007 and 2008, and finds that over 27 percent of non-group affiliated insurers engage in short-term equity trading activity. When it comes to the medium of short-term equity trading, stocks categorized as Industrial and Miscellaneous Stocks are the most frequently utilized with Financial Institutions' stocks a distant second. This is due to a larger number of stocks falling under these two categories. However, in terms of the mean size of transactions, the average investment in preferred stock ranges from four to five times larger than that of common stocks during the period of interest in this study. The mean holding period for short-term common equity transaction is about 100 and 95 days in 2007 and 2008, respectively. We also identify factors associated with P/C insurers' short-term equity trading behavior. Logistic regressions show that financial variables are more strongly tied to insurers' short-term equity trading behavior than underwriting and demographic variables.
Keywords: G11; G22; G31; 330; institutional investors; property-casualty insurers; investment decision